Blood Pressure Monitoring in Cardiovascular Medicine and Therapeutics - White, William B. (Clinical Hypertension and Vascular Diseases, 2007)
In this newly updated second edition of Blood Pressure Monitoring in Cardiovascular Medicine and Therapeutics, William B. White, MD, and a panel of highly distinguished clinicians give a critical review of every aspect of the evaluation of high blood pressure. This includes home and ambulatory blood pressure monitoring, the relationship between whole-day blood pressure and the cardiovascular disease process, and the effects of antihypertensive therapies on these blood pressure parameters. World-class contributors describe the significant advances in our understanding of the circadian pathophysiology of cardiovascular disorders and demonstrate that ambulatory blood pressure values are independent predictors of cardiovascular morbidity and mortality. This book provides a comprehensive up-to-date resource of this dynamic field in hypertension and vascular disease.